Financial Ratio Analysis to Predict Financial Distress at PT. Perkebunan Nusantara IV (Persero) Medan - Febri Bahri; Rahima Br. Purba; Oktarini Khamilah (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This study is entitled "Financial Ratio Analysis to Predict Financial Distress Conditions at PT. Perkebunan Nusantara IV (Persero) Medan”. This study aims to analyze the ratio of leverage (Debt to equity ratio), liquidity (Current ratio) and profitability (Return on Assets) to predict financial distress at PT. Perkebunan Nusantara IV (Persero) Medan during the 2017-2019 period. This research was conducted using descriptive method with the employment of secondary data. This study also aims to determine the level of financial performance of SOEs (BUMN) based on the Decree of the Minister of State-Owned Enterprises No: KEP-100/MBU/2002 concerning the assessment of the financial health of SOEs. This study usedseveral ratio indicators, namely, Return on equity, Return on investment, Cash ratio,Collection period, Inventory turnover, Total assets turnover, and Total equity to total assets. Based on the results, PT. Perkebunan Nusantara IV (Persero) Medanobtained the health level of BB (Less Healthy). The results also showed that the leverage, liquidity and profitability ratio variables could predict financial distress at PT. Perkebunan Nusantara IV (Persero) Medan.